Study Individual Differences Of Explosive Force According To Variables (age And Gender) Of Handball Players Junior Category - A Field Study On Wilaya Of Algiers Association Clubs . - Ikene, Soumaya (جامعة الوادي - University of Eloued, 2023)
The study aimed to determine the individual differences of explosive power according to the variables (age and gender) of handball players of the middle class, and the researcher used the descriptive and analytical approach, and the research sample included (16) players divided into 8 players 18 years old and 08 players 16 years old and from Each category 04 males and 04 females were chosen in an intentional way. The researcher used explosive force tests for the upper and lower extremities, and the statistical program Spss was used to analyze the results of the study. In the end, it was concluded that there are individual differences in the explosive power of handball players according to the difference in age and gender, a middle class, and accordingly the researcher recommended the need to pay more attention to the explosive power of the players during training sessions and to work on individual training according to the capabilities of each player, and to conduct more studies on the explosive power in various Other individual and team sports.
article
Keywords: explosive power , variables (age and gender) , handball players